Exploring the relationships among interpersonal competence, perceived stress and cognitive reappraisal in Chinese PAP recruits: a longitudinal cross-lag study - Sun, Liyun; Li, Min (Frontiers in Psychology, 2026)
BackgroundThe associations among interpersonal competence (IC), cognitive reappraisal (CR) and perceived stress (PS) among recruits of the Chinese People’s Armed Police Force (PAP) are poorly understood. The aim of this study is to clarify the relationships among these variables over time.MethodsA three-wave longitudinal study involving 300 recruits of the PAP surveyed over 3 months was conducted. The Chinese version of the Perceived Stress Scale (CPSS), the Brief Interpersonal Competence Questionnaire (ICQ-15), and the cognitive reappraisal scale, excerpted from the Emotion Regulation Questionnaire (ERQ), were chosen to assess PS, IC and CR. Longitudinal connections between these variables were examined via structural equation analysis.ResultsOur results revealed that time 1 IC negatively predicted time 2 PS and that time 1 PS negatively predicted time 2 IC. Time 1 IC positively predicted time 2 CR, time 2 IC positively predicted time 3 CR, time 1 PS negatively predicted time 2 CR, and time 2 PS negatively predicted time 3 CR.ConclusionThese findings highlight the role of IC in initiating stress and cognitive reappraisal. In this study, IC decreased PS and improved CR temporally. Therefore, the interpersonal competence of PAP recruits needs to be cultivated.